Avaliação do desempenho docente: o curso de Educação Física - OLIVEIRA, Suéllen Cristina Vaz de (2014)
The teacher performance assessment of formative mode, as seen in this study, gives an understanding of professional practice, enabling the improvement of their educational intentions and actions. Analyze the views of teachers and university students from the Physical Education on the evaluation of teaching performance has been the goal of this study. To achieve this purpose, this study presents two phases: the first characterized by a literature review discusses the formation, operation and assessment of teacher performance. The second stage involves the collection of data through a questionnaire with 26 teachers and 160 students from two institutions of higher education located in Minas Gerais, one public and one private. For analysis and interpretation of the data obtained the Content analysis: technical preparation and Analysis of units of Meaning proposed by Moreira, Simões and Porto (2005) was used. The results show that 17 teachers know the assessment tool used by the school nine unaware. We noticed also, that 77 students have not participated in this evaluation process. For teachers the goals of performance evaluation are: ignorance (eight); improvements (seven); highlight limitations (six), control (five), return (two) and reflection (two). As for the students to review aims: to evaluate (88), targeting improvements (47), provide feedback (27); ignorance (11) and failure (ten). Regarding teacher opinion on this mechanism, we find: important (17), failure (nine), diagnosis (nine) and promotes improvement (six) and for students: important (54), feedback (41), failure (28), ignorance (17), change (16) and diagnosis (seven). We found that the practice of 20 teachers have been changed due to the results of the performance evaluation, and 06 did not. A total of 143 students did not notice any change in teaching practice after completion of the review, 10 mentioned that yes and 7 left blank this question. We find positive and negative aspects related to teaching and student perspective on performance assessment, reaffirming the need for preparation and awareness of both. This preparation, it should approach since the presentation of the evaluation method used, providing an understanding of the real purpose of this, aiming to increase the number involved in this process, to really influence positively on educational performance, and perceptual for the pupils, both changes as the influence of this in their training. It is our expectation that the formative reflection on teacher performance assessment, this study and others, is constant. Do not just take the intent of the proposal is not constantly reflect on this mechanism, aiming at the contribution it can bring to all.